Lecithin-Linker Microemulsion Gelatin Gels for Extended Drug Delivery - Yu-Ling Cheng; Xiao-Yue Xuan; Edgar Acosta (MDPI AG, 2012)
This article introduces the formulation of alcohol-free, lecithin microemulsion-based gels (MBGs) prepared with gelatin as gelling agent. The influence of oil, water, lecithin and hydrophilic and lipophilic additives (linkers) on the rheological properties and appearance of these gels was systematically explored using ternary phase diagrams. Clear MBGs were obtained in regions of single phase microemulsions (μEs) at room temperature. Increasing the water content in the formulation increased the elastic modulus of the gels, while increasing the oil content had the opposite effect. The hydrophilic additive (PEG-6-caprylic/capric glycerides) was shown to reduce the elastic modulus of gelatin gels, particularly at high temperatures. In contrast to anionic (AOT) μEs, the results suggest that in lecithin (nonionic) μEs, the introduction of gelatin "dehydrates" the μE. Finally, when the transdermal transport of lidocaine formulated in the parent μE and the resulting MBG were compared, only a minor retardation in the loading and release of lidocaine was observed.